Mixed-Dimensional Coupling for Parallel Partitioned Nonlinear Finite-Element Analysis - Izzuddin, Bassam A.; Jokhio, Gul A. (ASCE, 2016)
This paper presents a novel mixed-dimensional coupling method for parallel partitioned analysis, allowing efficient nonlinear structural analysis with selective deployment of differently dimensioned elements. With this method, a structural domain is decomposed into partitions that are processed in parallel using a recently developed dual super-element partitioning approach. Individual partitions consist exclusively of reduced dimensioned (1D) or higher dimensioned (3D continuum) elements, and coupling between 1D and 3D partitions is introduced at the boundary of 3D partitions, enabling a reduction in the communication overhead. Several examples are provided to verify the proposed approach and demonstrate its benefits for nonlinear structural analysis.